2012
DOI: 10.1002/bdra.23011
|View full text |Cite
|
Sign up to set email alerts
|

Region 8q24 is a susceptibility locus for nonsyndromic oral clefting in Brazil

Abstract: BACKGROUND: Nonsyndromic cleft lip with or without cleft palate is a relatively common craniofacial defect with multifactorial inheritance. The association of the rs987525 single nucleotide variant, located in a gene desert at 8q24.21 region, has been consistently replicated in European populations. We performed a structured association approach combined with transcriptional analysis of the MYC gene to dissect the role of rs987525 in oral clefting susceptibility in the ethnically admixed Brazilian population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 40 publications
6
37
0
3
Order By: Relevance
“…It is thus possible that CLO etiology might be genetically more homogenous than CLP, that is, only one or a few molecular pathways are deregulated among CLO patients. We previously reported on a positive association of rs987525 SNP (8q24.21) in Brazil, driven by a subpopulation of patients with the highest heritability estimates (from Barbalha; H 2 ¼ 85%) as compared to other four regions of Brazil (Santar em, Fortaleza, Macei o, and Rio de Janeiro presented H 2 ¼ 45-71%; [Brito et al, 2012]). A stratified analysis by region of origin in the present study did not reveal a strong association with any group (Supplementary eTable I-See Supporting Information online), however, we observed a trend of positive association only in the Barbalha subset (Barbalha, P ¼ 0.02; Santar em, P ¼ 0.59; Fortaleza, P ¼ 0.66; Macei o, P ¼ 0.44; Rio de Janeiro, P ¼ 0.69).…”
Section: Discussionmentioning
confidence: 96%
“…It is thus possible that CLO etiology might be genetically more homogenous than CLP, that is, only one or a few molecular pathways are deregulated among CLO patients. We previously reported on a positive association of rs987525 SNP (8q24.21) in Brazil, driven by a subpopulation of patients with the highest heritability estimates (from Barbalha; H 2 ¼ 85%) as compared to other four regions of Brazil (Santar em, Fortaleza, Macei o, and Rio de Janeiro presented H 2 ¼ 45-71%; [Brito et al, 2012]). A stratified analysis by region of origin in the present study did not reveal a strong association with any group (Supplementary eTable I-See Supporting Information online), however, we observed a trend of positive association only in the Barbalha subset (Barbalha, P ¼ 0.02; Santar em, P ¼ 0.59; Fortaleza, P ¼ 0.66; Macei o, P ¼ 0.44; Rio de Janeiro, P ¼ 0.69).…”
Section: Discussionmentioning
confidence: 96%
“…Similar results for rs987525 were obtained in a study on the Central European sample which showed a 1.7-fold increase in the risk of nsCL/P under the dominant inheritance model 19 . Although the association between rs987525 and the risk of nsCL/P has been replicated in numerous studies on various ethnicities [28][29][30][31] , the underlying functional mechanism remains unknown as rs987525 resides in a region of the genome containing no known genes 12 . It is possible that rs987525 or a linked causal SNP affects tissue-specific enhancers, altering the expression of one or more unspecified genes.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have used a structured association approach, which takes advantage of information on individual ancestry components of cases and controls before performing the association tests. Differently from our previous reports (Brito et al, 2012a;Brito et al, 2012c) we used here an AIM panel composed of biallelic SNPs and a larger sample set.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The association of the top-SNP rs987525 has been consistently replicated in populations from Europe (Cura et al, 2015), Central America (RojasMartinez et al, 2010), Brazil (Brito et al, 2012c) and Middle-East (Aldhorae et al, 2014).…”
Section: Box1: 8q24 Locusmentioning
confidence: 92%